Switzerland and Sub-Saharan Africa in the Cold War, 1967-1979 Neutrality Meets Decolonisation - Widmer, Sabina (New Perspectives on the Cold War, 2021)
In this volume Sabina Widmer analyses neutral Switzerland's foreign policy in Angola, Mozambique, Ethiopia, and Somalia during the armed conflicts and regime changes of the late 1960s and 1970s, in a context of global Cold War and decolonisation.; Readership: All interested in Swiss foreign policy after 1945, neutrality during the Cold War, Africa in the Cold War, and European politics towards Africa.